Novel melamine – salicylic salt solvates and co-crystals; an analysis of the energetic parameters of the intermolecular hydrogen bonds stabilizing the crystal structure. Issue 32 (30th June 2022) - Wzgarda-Raj, Kinga; Rybarczyk-Pirek, Agnieszka J.; Wojtulewski, Sławomir; Palusiak, Marcin
Abstract : A pseudopolymorphism of two novel melamine – salicylic complexes and an example of a salt co-crystal structure. Abstract : Two novel crystal structures based on melamine and salicylic acid, with either water (I ) (4 : 3 : 8 molecular ratio) or ethanol (II ) (2 : 2 : 1 molecular ratio), can be treated as salt solvates. In these structures, all molecular components are bound by expanded hydrogen bonding networks consisting of N–H⋯N, N–H⋯O, O–H⋯O, and O–H⋯N interactions among the solvent molecules and acid–base complexes; these stabilize the crystal architecture. Special attention is paid to the N + –H⋯O − hydrogen bonds formed between cationic melamine molecules and the ionized carboxyl group (COO − ) of anions of salicylic acid. These salt bridges exist as single contact or bifurcated double donor/acceptor hydrogen bonds which are additionally accompanied by N–H⋯O interactions. This present study uses quantum chemistry methods (DFT, QTAIM) to understand their nature and their energetic parameters.